Standardization of drip-based fertigation scheduling in cucumber grown under protected conditions - THAKUR, MONICA; JASWAL, RICHA; SANDAL, SANJEEV K (Journal of Soil and Water Conservation, 2025)
The effectiveness of naturally ventilated polyhouse is influenced by the irrigation system that is set up. This study assessed the effects of different drip irrigation levels and fertigation methods on cucumber growth, water use efficiency, and productivity in a naturally ventilated polyhouse at CSK HPKV, Palampur, during 2013 and 2014. The treatments included two drip irrigation levels: I0.4 (40% PE) and I0.8 (80% PE). Additionally, four fertigation levels were tested: F50 (50% of recommended NPK doses), F100 (100%), F150 (150%), and F200 (200%). A control treatment with 100% NPK applied conventionally and drip irrigation at 1.0 PE, along with a farmer’s practice treatment 10 gm-2 IFFCO (12:32:16 as basal)+ 2 g L-1 of 19:19:19 as fertigation at 15 days interval & drip irrigation applied at rates 2 Lm-2 daily, were also included. Cucumber crops were transplanted on July 16, 2013 (Crop I), October 10, 2013 (Crop II), and March 26, 2014 (Crop III). Results showed that the I0.8 treatment maintained higher soil water content and produced better marketable fruit yield and water use efficiency compared to I0.4 and the control. Specifically, fertigation at 150% and 200% RDF at the 0.8 PE level resulted in the highest marketable yield and benefit-cost ratio. However, irrigation at the 0.4 PE level demonstrated the highest water use efficiency, highlighting significant water savings. Principal Component Analysis (PCA) explained over 80% of data variability, indicating that treatment differences significantly influenced the variables studied.